Conversational Imperative in Ma’laqa al-A’sha: A Deliberative Approach - Abboud, Shaima Hatem (Journal of Tikrit University for Humanities, 2024)
Language philosophers coined the term conversational implicature, which has become a feature of modern lessons and a critical approach to discourse analysis. The theory of conversational imperative aims to identify the connotations of words and reveal their indirect meanings and purposes. The scientist (Grice) establishes the foundation of speaker-listener discussion (the principle of collaboration). He then established a set of communication rules and principles, including the principle of quantity, the principle of how, the principle of appropriateness, and the principle of method or method, to control and succeed the communicative process, which pragmatics scholars sought to find and enable interlocutors to communicate and reach a successful dialogue. Conversational implication describes and interprets, allowing the speaker to mean more than what he says and the addressee to understand rhetorical utterances.